Introduction - Faidra Filippidou (A+BE: Architecture and the Built Environment)
The rapid growth of urban areas has led to the unsustainable use of resources (Langeweg et al. 2000; Bhatta 2010; UN 2014). The impacts of urban areas are evident in regions which supply cities with food, water, energy and absorb pollution and waste (UN 2014). At the same time, the current world population, of 7.6 billion, is predicted to reach 8.6 billion in 2030 and 9.8 billion in 2050 (UN 2017). Moreover, the urban population, in 2014, accounted for 54% of the total global population. This signifies a 20% increase since 1960. In 2014, the majority of people - 54% - were living in urban areas and this percentage is estimated to rise in the future (WHO 2017). In Europe, 72.5 % of European Union (EU)-28 countries inhabitants lived in cities, towns and suburbs in 2014 (Eurostat 2016b). Nevertheless, differences between countries exist. Figure 1.1 shows the urban population growth of the Netherlands in comparison to the EU, Germany, Spain, France, Slovenia and Sweden. The Netherlands is characterised by a high level of population density and a high share of urban land use, whereas in most of the Scandinavian countries and Spain much lower levels of urban land use are present (Eurostat 2016b).